2018
DOI: 10.1016/j.prosdent.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cement type and ceramic primer on retention of polymer-infiltrated ceramic crowns to a one-piece zirconia implant

Abstract: Products containing MDP provided a high chemical bond to zirconia. Self-adhesive and adhesive resin cements with low chemical bonding capabilities to zirconia provided retention force values within a small range (220 to 290 N).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 38 publications
5
34
0
Order By: Relevance
“…Due to differences in test set-ups, the retrieved fracture load [10][11][12][13][14][17][18][19][20] or retention force [21,22] values can vary greatly for the respective materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to differences in test set-ups, the retrieved fracture load [10][11][12][13][14][17][18][19][20] or retention force [21,22] values can vary greatly for the respective materials.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, another study by Rohr, Nadja, Brunner, et al 11 found that resin based temporary cement showed significantly higher retentive values than those of the zinc oxide non eugenol temporary cement when used with polymer infiltrated hybrid glass ceramic crowns supported by one piece zirconia implants 11 . However, in their study they have done surface treatment to the fitting surfaces of the crowns, which maybe the reason of the significant higher retentive values of the resin based temporary cement than those of the zinc oxide non eugenol temporary cement.…”
Section: Discussionmentioning
confidence: 95%
“…An interaction between the hydroxyl groups of 10-MDP in F2.0 and the cationic surface of resin block was able to form a strong bond between resin cement and resin block. Previous studies have suggested that while V5 has good dentin bonding ability 16) , V5 shows inferior bonding performance to prosthetic materials when comparing V5 to F2.0 24) .…”
Section: Discussionmentioning
confidence: 97%